Visual and melanopic performance of a tropical daylight-mimicking lighting: a case study in Thailand - Somyod Santimalai; Thavatchai Tayjasanant (Institute of Advanced Engineering and Science, 2023)
This paper designed and developed a tropical daylight-mimicking lighting system based on photometric, radiometric, and International Commission on Illumination (CIE) standard melanopic performances from natural lighting cycles in Thailand. Spectral power distribution (SPD) during daylight in summer and winter were recorded to create a dynamic artificial lighting system that best matches the natural daylight characteristics. Two set-ups light emitting diode (LED) (LED-A and LED-B) were screened, developed, validated, and compared with different chromaticity layouts of the correlated color temperatures (CCTs) allocated on Planckian locus and later converted to x-y co-ordinates in a chromaticity diagram. Based on CCT and Duv deviations between two developed setups, LED-A could mimick circadian points on the chromaticity diagram better than LED-B did. CCT and Duv values of LED-A (dCCT=3.75% and dDuv=17.36%) can match closer to the daylight than those of LED-B (dCCT=5.0% and dDuv=56.84%). For CIE-standard melanopic performances (melanopic efficacy of luminous radiation (mELR), melanopic equivalent daylight (D65) illuminance (mEDI) and melanopic daylight efficacy ratio (mDER)), LED-A is suitable to use indoor with averages of 1.16 WÃ—lm-1, 236 lx and 0.84, respectively, while LED-B is good to use outdoor with averages of 1.53 WÃ—lm-1, 266 lx and 1.06, respectively. The proposed design can be used as a guideline to establish a daylight-mimicking LED lighting system from actual measurement data.